Trace metal concentrations in the different parts of Perna viridis collected from some jetties in the straits of Johore. - Ng, Eugene Y. J.; Yap, Chee Kong; Zakaria, Mohamad Pauzi; Aris, Ahmad Zaharin; Tan, Soon Guan (Enviro Media, 2013)

(untitled)
The Straits of Johore is a hotspot area of metal pollution in the southern part of PeninsularMalaysia. In this study, green-lipped mussels Perna viridis were collected from three sites from theStraits of Johore in April 2011. The mussel tissues were dissected into eight parts including byssus,crystalline style, foot, gill, gonad, mantle, muscle and remainder. The total shells and all thedissected eight parts were determined for nine trace metal concentrations (Ag, As, Co, Cr, Cs, Hg,Mn, Se and Sr) by using an Inductively Coupled Plasma-Mass Spectrometer, because these ninetrace metals are rarely reported in the literature from Malaysia. Based on the present data, Sr andMn have a very different accumulation pattern in mussels when compared with other trace metals.It is also found that the byssus is highly accumulative of Co and Cr, while the shell is also highlyaccumulative of for Sr. When compared to the metal levels reported in the literature, the presentdata are considered low. Further studies are needed to confirm why Gelang Patah population hadthe highest levels of Ag, As, Cs, Mn and Se when compared to Senibong and Pantai Lido, basedon some mussel parts. The present data in the different tissues of P. viridis are important for futurereference.